Circular Economy- Based Business Model With Business Model Canvas For Keris Craftsmen In Sumenep Madura - Hidayat, Nurul; Najiatun, Najiatun; Anshori, Syaiful Anshori; Nabilatul Hasanah (Eqien - Jurnal Ekonomi dan Bisnis, 2026)
Tourist Village Aeng Tong-Tong, Sumenep, as center the largest keris craftsman recognized by UNESCO, has potential big in business model development sustainable based circular economy. Research This aim designing and redesigning business models with approach Business Model Canvas (BMC), evaluates potential revenue stream new, and study sustainability model for keris craftsman. Using method qualitative exploratory with technique expert opinion and key informant interviews, research This compile existing BMC, design Circular Business Model Canvas (CBMC), as well as analyze eligibility income new and diversified product based waste production. Research results show that integration principle circular economy in BMC increases efficiency source power, reduce waste, and produce product derivative worth plus. Digital marketing, NFT technology and green marketing participate strengthen Power competition keris industry. Research This offer contribution to development craft- based industry culture in a way sustainable with integration draft circular economy in context local.